Five new species of the genus Rhyacophila Stephens (Trichoptera, Rhyacophilidae) from southwestern Hokkaido, northern Japan - Ito, Tomiko; Kuhara, Naotoshi; Malicky, Hans (Zootaxa, 2024)
Five new species of the genus Rhyacophila Stephens (Trichoptera: Rhyacophilidae) are described mainly based on adults from southwestern Hokkaido, northern Japan: R. eniwa Ito & Kuhara sp. nov. of the R. sibirica Species Group, R. bifue Ito & Kuhara sp. nov., R. imakane Ito & Kuhara sp. nov. and R. misago Ito & Kuhara sp. nov. of the R. kalkatica Species Group, and R. shimamaki Ito & Kuhara sp. nov., of an unknown species group. Also reported are records of R. arefini Lukyanchenko, a species similar to R. eniwa sp. nov., and R. hamata Hattori & Ohkawa, a species similar to the three new species of the R. kalkatica Species Group.